Domestikasi ideologi dalam penerjemahan Injil: Inggris-Bali - Brata, Frans I Made (citeus, 2011)
The Bible’s translator expects his translation to be not only accurate, but also acceptable in accordance with the norms and cultural values of its readers. This study aims to describe the domesticating ideology in translation. Tu–Vous Theory combined with Attitude, as part of Appraisal Theory in Systemic Functional Linguistics, is used to investigate how words should be used. Dynamic Equivalence Theory is utilized to describe word usage in society. A descriptive qualitative approach in determining two principal orientations of translation techniques, methods, and ideologies was applied in analyzing the data. Questionnaires containing sentences with English terms of address in Luke’s Bible and their equivalents in Balinese were used to verify the data. The findings show that the domesticating ideology has a positive contribution to the quality of the translation with regard to its accuracy, acceptability, and readability.